Implementasi Metode Pembelajaran Storytelling pada Program Distance Learning Peserta Didik Paket A di PKBM Homeschooling Kak Seto Surabaya - Rahmawati, Naila; Nugroho, Rivo (J+PLUS UNESA, 2024)
This research purpose of to describe and analyze the implementation of the storytelling learning method in the distance learning program for package A students at the Kak Seto Homeschooling community learning center in Surabaya; Describe and analyze the experiences of students package A in realizing the storytelling learning method at the Kak Seto Surabaya Homeschooling community learning center; Describe and analyze learning outcomes by applying the storytelling learning method in the distance learning program at the Kak Seto Homeschooling community learning center in Surabaya. This type of research approach uses descriptive with qualitative methods. This research uses data collection techniques through observation data, interviews and documentation. The data validity tests used are credibility tests, transferability tests, dependability tests, confirmability tests. This research data analysis technique uses data reduction, data presentation and drawing conclusions. The results of this research found that by applying the storytelling learning method, students were more enthusiastic about learning and according to the tutor, by applying the storytelling learning method they felt that the learning process was running effectively. During the process of realizing this storytelling learning method, tutors involve online distance learning students in the learning process, so that students have practical experience and prefer the learning process and find it easy to understand the material because they feel connected to relevant stories according to the students' experiences. That way, students have maximum learning outcomes and students have a significant increase in understanding of the material that has been delivered by the tutor.